1993
DOI: 10.1021/bi00097a014
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of the three major subclasses of lipoprotein A-I preparatively isolated from human plasma

Abstract: Apolipoprotein (apo) A-I is the major protein constituent of plasma high-density lipoproteins (HDL). HDL consist of two major classes of apoA-I-containing lipoproteins: LpA-I and LpA-I:A-II. LpA-I includes heterogeneous lipoprotein particles that differ in size and hydrated density. LpA-I was isolated by immunoaffinity chromatography from the fasting plasma of 24 normal human subjects and separated by gel filtration chromatography. Three major subclasses of LpA-I were eluted: large (Lg-LpA-I), medium (Md-LpA-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 58 publications
(66 reference statements)
3
24
0
Order By: Relevance
“…In contrast, small spherical particles containing only apoA-I represent the majority of the LpA-I particles in the plasma of LCAT-deficient patients. These particles are similar in size to those isolated from normal plasma (66) and are catabolized at a rate similar to that of small LpA-I particles in normal subjects. Given their size, lipid, and apolipoprotein composition, these small particles may be important in promoting cholesterol efflux from cells and maintaining effective reverse cholesterol transport in LCAT-deficient patients.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast, small spherical particles containing only apoA-I represent the majority of the LpA-I particles in the plasma of LCAT-deficient patients. These particles are similar in size to those isolated from normal plasma (66) and are catabolized at a rate similar to that of small LpA-I particles in normal subjects. Given their size, lipid, and apolipoprotein composition, these small particles may be important in promoting cholesterol efflux from cells and maintaining effective reverse cholesterol transport in LCAT-deficient patients.…”
Section: Discussionmentioning
confidence: 67%
“…These combined results indicate that there are two major classes of HDL particles in classic LCAT deficiency and Fish-eye disease: large discoidal particles in the HDL2 density range containing apoA-I and apoA-II, and small spherical particles in the small HDL3 to d > 1.21 g/ml range containing apoA-I without apoA-II. The small particles containing only apoA-I resemble small LpA-I particles preparatively isolated from normolipidemic subjects (66). It has been suggested that the HDL isolated from LCAT-deficient patients may represent nascent HDL particles.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein cholesterol profiles were obtained by fast protein liquid chromatography as described (17). This system allows separation of the three major lipoprotein classes; VLDL, low density lipoproteins, and HDL.…”
Section: Methodsmentioning
confidence: 99%
“…Lecithin-cholesterol acyltransferase (LCAT)' is a 416-amino acid glycoprotein produced mainly by the liver that circulates in the plasma compartment as a functional unit with the cholesteryl ester transfer protein (CETP) and apo AI and apo D primarily in the HDL density range (2,3). LCAT, through its role in the esterification of cholesterol, promotes the packaging of this polar lipid into the core of the HDL particles, maintaining a concentration gradient for the diffusion of free cholesterol from peripheral tissues to HDL.…”
mentioning
confidence: 99%